The Effect of Strategic Supplier Partnership on Supply Chain Integration, Supply Chain Performance and Farmers Performance - Miranti Sedyaningrum; Arik Prasetya; Muhammad Kholid Mawardi (Wacana Journal of Social and Humanity Studies, 2019)
This research was conducted to examine the effect of strategic supplier partnerships on the the supply chain integration, supply chain performance and farmers performance. This research is an explanatory research with a quantitative approach. The data was collected using Â questionnaires. The sampling method was multistage proportional random sampling of 200 respondents. Data analysis in this study used path analysis method with help by SPSS. The results of this study indicate that strategic supplier partnerships have no significant effect on supply chain integration, supply chain performance and farmers performance. The supply chain integration has a significant positive effect toward supply chain performance and farmers performance. While the supply chain performance has a significant positive effect toward farmers performance.